Prodromal Parkinson's disease as defined per MDS research criteria in the general elderly community. Issue 9 (6th June 2016) - Mahlknecht, Philipp; Gasperi, Arno; Willeit, Peter; Kiechl, Stefan; Stockner, Heike; Willeit, Johann; Rungger, Gregorio; Sawires, Martin; Nocker, Michael; Rastner, Verena; Mair, Katherina J.; Hotter, Anna; et al.
Abstract: Background: Recently, the International Parkinson and Movement Disorder Society has defined research criteria for prodromal Parkinson's disease (PD), but to date their predictive value has not yet been tested in population‐based cohorts. Methods: We retrospectively applied these criteria to the longitudinal Bruneck Study cohort aged 55‐94 years using recorded data on all included risk and prodromal markers that are quick and easily assessable. Results: After excluding participants with idiopathic PD or secondary parkinsonism, prevalence of probable prodromal PD in the remaining 539 participants was 2.2% (95% confidence interval, 1.2%‐3.9%). Of 488 participants followed up over 5 years, 11 developed incident PD. Sensitivity of "probable prodromal PD" status for incident PD was 54.6% (95% confidence interval, 28.0%‐78.8%), specificity was 99.2% (97.8%‐99.8%), positive predictive value was 60.0% (31.2%‐83.3%), and negative predictive value was 99.0% (97.5%‐99.6%). Conclusions: Our findings suggest that the new research criteria for prodromal PD are a promising tool to identify cases of incident PD over 5 years, arguing for their usefulness in defining target populations for disease‐prevention trials. © 2016 International Parkinson and Movement Disorder Society